2020
DOI: 10.1093/aje/kwaa247
|View full text |Cite
|
Sign up to set email alerts
|

How Long-Term Acute Care Hospitals Can Play an Important Role in Controlling Carbapenem-Resistant Enterobacteriaceae in a Region: A Simulation Modeling Study

Abstract: Typically, long-term acute care hospitals (LTACHs) have less experience in and incentives to implement aggressive infection control for drug-resistant organisms such as carbapenem-resistant Enterobacteriaceae (CRE) than acute care hospitals. Decision makers need to understand how implementing control measures in LTACHs can impact CRE’s spread regionwide. Using our Chicago metropolitan region agent-based model to simulate CRE’s spread and control, we estimated that a prevention bundle in only LTACHs decreased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…spread. [20][21][22][23][24] Thus, these sustained efforts at LTACH-A may provide considerable benefits to the broader region.…”
Section: Discussionmentioning
confidence: 99%
“…spread. [20][21][22][23][24] Thus, these sustained efforts at LTACH-A may provide considerable benefits to the broader region.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in these facilities have been shown to be colonized with CRE at high rates, likely due to a combination of their chronic severe illness, long lengths of stay, and high rates of prior or on-going antibiotic exposure. Modeling and epidemiologic studies have suggested that the high CRE prevalence in LTACHs in particular has a significant impact on connected healthcare facilities with which they share patients [7,8]. Currently, less is known about the regional influence of vSNFs, although the even longer lengths of patient stay and more limited resources for infection prevention indicate that they might also be important settings in regional amplification of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Patients in these facilities have been shown to be colonized with CRE at high rates, likely due to a combination of their chronic severe illness, long lengths of stay, and high rates of prior or ongoing antibiotic exposure. Modeling and epidemiologic studies have suggested that the high CRE prevalence in LTACHs in particular has a significant impact on connected healthcare facilities with which they share patients [ 7 , 8 ]. Currently, less is known about the regional influence of vSNFs, although the even longer lengths of patient stay and more limited resources for infection prevention indicate that they might also be important settings in regional amplification of antibiotic resistance.…”
mentioning
confidence: 99%